The Analysis of Students' Creative Thinking Abilities in View of Mathematics Anxiety Levels in Class IX of Junior High Schools - Indah Sari; Abdul Rahman; Rosidah (PT ARRUS Intelektual Indonesia, 2024)
This research is qualitative research with phenomenological research methods. Phenomenological research is a type of qualitative research that deeply examines individuals' explanations and understandings of their experiences. The subjects of this study were 4 (four) grade IX students. Data collection techniques in this study were questionnaires, tests, and interviews. The research instruments used are a questionnaire of math anxiety level, creative thinking ability test, andi nterview guidelines. Data analysis techniques in this research include data condensation, datap resentation, and conclusion drawing. Students with low anxiety level were able to fulfill all four indicators of creative thinking ability, while students with high anxiety level were only able to fulfill two indicators of creative thinking ability.